A mitochondria-targeted ratiometric NIR fluorescent probe for simultaneously monitoring viscosity and ONOO− based on two different channels in living HepG2 cells. (February 2023) - Liu, Qingqing; Dong, Chao; Zhang, Jing; Zhao, Bo; Zhou, Yongqing; Fan, Chunhua; Lu, Zhengliang
Abstract: Mitochondrial viscosity and ONOO − are involved in various pathological and physiological processes. Abnormal viscosity or irregular ONOO − concentration would disrupt the normal function of cells. Hence, we skillfully designed and synthesized a dual-responsive probe Mito-HC-TZ for the simultaneous detection of ONOO − and viscosity by different channels. 3-ethylbenzothiazolium was acted as fluorescent rotor to regulate the twisted intramolecular charge transfer (TICT) process; the C = C of 3-ethylbenzothiazolium linked to the xanthene core could be easily broken by ONOO − . Thus, the probe responded to viscosity and ONOO − by red and orange fluorescence channels, respectively. Mito-HC-TZ had high selectivity, low cytotoxicity and wide range of pH values. The results of cell imaging experiments showed the probe could be used to respectively monitor the viscosity and ONOO − level in HepG2 cells. Graphical abstract: Image 1 Highlights: A NIR probe for viscosity and ONOO − according to two channels was developed. Mito-HC-TZ could ratiometrically respond to mitochondrial viscosity and ONOO − . Mito-HC-TZ was applied to detect the changes of viscosity and ONOO − in cells.